Личный убийца: [роман] / О. И. Приходько - Приходько Олег Игоревич (Черная кошка, 1998)
Экземпляры: АБ (20190109) / Инвентарный номер: 31559 / Цена: 21.00 / Сис.шифр: 84 (2Рос=Рус)6 / Авт.знак: П 77 / ГРНТИ: 17.82.31 / ББК: 84 (2Рос=Рус)6